Effect of once‐weekly exenatide on estimated glomerular filtration rate slope depends on baseline renal risk: A post hoc analysis of the EXSCEL trial - van der Aart‐van der Beek, Annemarie B. (Diabetes Obes Metab, 2020)
The effects of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) on renal outcomes in patients with type 2 diabetes at high cardiovascular risk are modest or neutral. However, GLP‐1RAs may confer clinical benefits in those at high risk of progressive renal function loss. We examined the effects of once‐weekly exenatide (EQW) on estimated glomerular filtration rate (eGFR) slope and urinary albumin:creatinine ratio (UACR) as a function of baseline UACR in 3503 EXSCEL participants (23.7%) with eGFR data available and 2828 participants (19.2%) with UACR change data available. EQW improved eGFR slope assessed via mixed model repeated measures, compared with placebo, in participants with baseline UACR >100 mg/g (0.79 mL/min/1.73 m(2)/year [95% confidence interval CI 0.24–1.34]) and UACR >200 mg/g (1.32 mL/min/1.73 m(2)/year [95% CI 0.57–2.06]), but not at lower UACR thresholds. EQW reduced UACR, compared with placebo, assessed via analysis of covariance, consistently across subgroups with baseline UACR >30 mg/g (28.2% reduction), baseline UACR >100 mg (22.5% reduction) and baseline UACR >200 mg (34.5% reduction). This post hoc EXSCEL analysis suggests that EQW reduces UACR, with improvement in eGFR slope specifically in participants with elevated baseline UACR.